Training prescription: The relationships of technique, overload, and specificity - Rushall, B. S. (1995)
Only training which affects the exact energizing components for particular movement patterns that arise in particular races will contribute to improved race performances. The corollary to this is, if competitive performances do not improve, then training has been maladaptive. Since competitive performances require a range of energy uses and movement patterns, that range needs to be stimulated in blocks of specific tasks. Adequate stimulation does not require excessive debilitating fatigue. The signal that training sets should be terminated is when both performance and movement precision deteriorate despite greater effort on behalf of the athlete. While these aspects of training stimulation: (a) specific race adaptation, (b) aerobic base maintenance, (c) moderate levels of overload, and (d) complete between-stimulations recovery, are used for exercise prescription, practice effects should accrue and result in improved racing performances of an optimally executed nature. If performance improvements do not occur in a seriously training athlete, then beneficial training effects have not been developed. Important sentences: Different training intensities use different physiological mechanisms and patterns of muscle stimulation and therefore, produce different training effects. For effective training at least the appropriate biomechanical actions (technique and its constituent neuromuscular pathways) must be maintained and repeated while the appropriate energy system is fatigued (but not to excessive levels). For specific training to be beneficial it has to include both the biomechanics and energizing system of the intended competitive performance. A response system can only be stimulated optimally when it is exposed to repetitive work that requires skill technique maintenance in the face of increasing fatigue. There comes a time in a training segment where further work in a fatigue state is counterproductive. There is a range of speeds enacted by an athlete in a race. If one element of the required "training range" is neglected then there will be a weakness in an athlete's preparation for a specific event. A range of training stimuli should be restricted to those which will be elicited in a performance. Incurring fatiguing stimuli which will not arise in a competition is a waste of time. However, there also has to be a considerable amount of training performed at a constant aerobic level over relatively long distances to maintain a solid aerobic base for training, not race performance, so that recovery is accelerated and specific training stimuli volume maintained and/or extended. A training session should consist of two emphases. First, training to race particular events. Second, training to maintain a fitness base that will support the highest volume of and quickest recovery from race-specific work. This latter feature could be described as "training to train." The frequency of training stimulations of a beneficial nature is solely determined by the time it takes to achieve full recovery between each stimulus exposure. In any competitive event, even one that is considered to be aerobic, the initial work is predominantly anaerobic.